Macondo oil in deep-sea sediments: Part 2 — Distribution and distinction from background and natural oil seeps. Issue 1 (15th October 2016) - Stout, Scott A.; Payne, James R.; Ricker, Robert W.; Baker, Gregory; Lewis, Christopher
Abstract: Following the Deepwater Horizon oil spill, the spilled Macondo oil was severely weathered during its transport within the deep-sea plume as discrete particles, which were subsequently deposited on the seafloor. The Macondo oil deposited in deep-sea sediments was distinguished from ambient (background) hydrocarbons and naturally-seeped and genetically-similar oils in the Mississippi Canyon region using a forensic method based upon a systematic, multi-year study of 724 deep-sea sediment cores collected in late 2010 and 2011. The method relied upon: (1) chemical fingerprinting of the distinct features of the wax-rich, severely-weathered Macondo oil; (2) hydrocarbon concentrations, considering a core's proximity to the Macondo well or to known or apparent natural oil seeps, and also vertically within a core; and (3) results from proximal cores and flocculent material from core supernatants and slurp gun filters. The results presented herein establish the geographic extent of "fingerprintable" Macondo oil recognized on the seafloor in 2010/2011. Highlights: Forensic analysis of over 700 cores reveals extent of Macondo oil on the seafloor. Spilled oil distinguished from naturally-seeped oils and background hydrocarbons. Spill-derived PAH and hopane concentrations decrease with distance from the well. Macondo oil in sediments was found up to 30 km southwest of the well.